Effect of Metformin Therapy on Reducing Leptin Resistance and Enhancing Ovulation in Women with Polycystic Ovary Syndrome - Tuama*, Wafaa Issa (AL-Kindy College Medical Journal, 2012)
Background: The relation between insulin resistance ,leptin levels and other hormones in women with polycystic ovary syndrome(PCOS) is still controversial.Metformin therapy is proved effective in reducing insulin resistance and also in some studies it was seen to be effective in reducing leptin levels. Al- Kindy Col Med J 2012 ; Vol .8 No. (2) p: 65 Objective: to study the effect of metformin on reducing leptin levels and enhancing ovulation in PCOS women. Methods:metformin 500mg 3 times daily for 3 months was was given to 36 women with proved PCOS, in addition to that, other parameters were included. Results:28 women out of 36(77.78%) showed an evidence of ovulation ovulation after 3 months of metformin therapy(p<0.01) with significant ◌ٌ reduction in leptin levels(p<0.001). Conclusion: it can be concluded that metformin can reduce leptin resistance and enhance ovulation in PCOS women.